Effects of genetic variation in H3K79 methylation regulatory genes on clinical blood pressure and blood pressure response to hydrochlorothiazide - Duarte, Julio D (BioMed Central, 2012)
BACKGROUND: Nearly one-third of the United States adult population suffers from hypertension. Hydrochlorothiazide (HCTZ), one of the most commonly used medications to treat hypertension, has variable efficacy. The renal epithelial sodium channel (ENaC) provides a mechanism for fine-tuning sodium excretion, and is a major regulator of blood pressure homeostasis. DOT1L, MLLT3, SIRT1, and SGK1 encode genes in a pathway that controls methylation of the histone H3 globular domain at lysine 79 (H3K79), thereby modulating expression of the ENaCα subunit. This study aimed to determine the role of variation in these regulatory genes on blood pressure response to HCTZ, and secondarily, untreated blood pressure. METHODS: We investigated associations between genetic variations in this candidate pathway and HCTZ blood pressure response in two separate hypertensive cohorts (clinicaltrials.gov NCT00246519 and NCT00005520). In a secondary, exploratory analysis, we measured associations between these same genetic variations and untreated blood pressure. Associations were measured by linear regression, with only associations with P ≤ 0.01 in one cohort and replication by P ≤ 0.05 in the other cohort considered significant. RESULTS: In one cohort, a polymorphism in DOT1L (rs2269879) was strongly associated with greater systolic (P = 0.0002) and diastolic (P = 0.0016) blood pressure response to hydrochlorothiazide in Caucasians. However, this association was not replicated in the other cohort. When untreated blood pressure levels were analyzed, we found directionally similar associations between a polymorphism in MLLT3 (rs12350051) and greater untreated systolic (P < 0.01 in both cohorts) and diastolic (P < 0.05 in both cohorts) blood pressure levels in both cohorts. However, when further replication was attempted in a third hypertensive cohort and in smaller, normotensive samples, significant associations were not observed. CONCLUSIONS: Our data suggest polymorphisms in DOT1L, MLLT3, SIRT1, and SGK1 are not likely associated with blood pressure response to HCTZ. However, a possibility exists that rs2269879 in DOT1L could be associated with HCTZ response in Caucasians. Additionally, exploratory analyses suggest rs12350051 in MLLT3 may be associated with untreated blood pressure in African-Americans. Replication efforts are needed to verify roles for these polymorphisms in human blood pressure regulation.